Rapid Multigram-Scale End-to-End Continuous-Flow Synthesis of Sulfonylurea Antidiabetes Drugs: Gliclazide, Chlorpropamide, and Tolbutamide - Sagandira, Cloudius R.; Watts, Paul (Synthesis, 2021)
A multigram-scale robust, efficient, and safe end-to-end continuous-flow process for the diabetes sulfonylurea drugs gliclazide, chlorpropamide, and tolbutamide is reported. The drugs were prepared by the treatment of an amine with a haloformate affording carbamate, which was subsequently treated with a sulfonamide to afford sulfonylurea. Gliclazide was obtained in 87% yield within 2.5 minutes total residence time with 26 g/h throughput; 0.2 kg of the drug was produced in 8 hours of running the system continuously. Chlorpropamide and tolbutamide were both obtained in 94% yield within 1 minute residence time with 184–188 g/h throughput; 1.4–1.5 kg of the drugs was produced in 8 hours of running the system continuously. N-Substituted carbamates were used as safe alternatives to the hazardous isocyanates in constructing the sulfonyl urea moiety.
Keywords: chlorpropamide; gliclazide; diabetes; end-to-end continuous flow; sulfonylurea; and tolbutamide